Cholecystectomy at the time of COVID-19: how pandemic changed surgical management - Montali, Filippo; Rigoni, Michela; Annicchiarico, Alfredo; Baldinu, Manuel; Virgilio, Edoardo; Costi, Renato (Acta Biomedica Atenei Parmensis, 2025)
Background: The COVID-19 pandemic had a huge impact on health services worldwide. Northern Italy was the first outbreak and one of the most affected areas of Europe. Most procedures were canceled or delayed. Surgeons were challenged to find the best management for patients. Surgery for benign conditions such as uncomplicated gallstone disease (UGD) was often given low priority in an elective setting. In literature there is little evidence of pandemic effects on routine surgical procedures in non-COVID-19 UGD patients.This study investigate the impact of COVID-19 pandemic on a cohort of patients tested negative for COVID-19 infection undergoing (elective and emergency) cholecystectomy in a secondary care hospital in northern Italy. Methods: A total of 200 patients were enrolled in the study. We compared two groups of 100 patients each undergoing cholecystectomy for symptomatic cholelithiasis in two different time frames: one before and one during the pandemic outbreak, respectively in 2019 and 2020. Pre-, intra-and post-operative features were evaluated. Results: There were statistically significantly higher preoperative blood levels of GOT (p=0.0164), GPT (p=0.0273) and ALP (p=0.0097) in the pre-pandemic group. Moreover, a significantly higher number of patients with acute biliary pancreatitis (AP) and common bile duct stones (CBDS) was detected in the pre-pandemic group (p=0.001). During the pandemic outbreak, significantly more cholecystectomies were performed by traditional approach (p=0.0001) and a shorter hospital stay was recorded. Conclusion: Patients undergoing cholecystectomy before COVID-19 pandemic showed a higher rate of AP and CBDS. A more conservative approach was preferred by surgeons.